Efficiency of subsowing of a lucerne in old-age artificial herbage at different modesof its use in the conditions of Yakutia - S. A. Pavlova; A. V. Kuzmina; E. S. Pestereva; N. N. Zhirkova (Аграрная наука Евро-Северо-Востока, 2018)
The research was conducted in 2004-2016 in the research and production station located 70 km higher Yakutsk on a terrace above flood-plain of the Lena river. The experiment is put on grass stand of the seventh year of growth. The basis of the stand consisted of the herbs, sown in 1997: Psathyrostachys juncea, Bromus inermis Leyss and Medicago falcata L. Soils of the experimental site are cryogenic, flood-plain, sod (steppificated). Studied was the efficiency of mineral nitrogen (N60-120) against the background of P60K60 and subsowing of a lucerne in cereal old-age herbage (at a sсarifiсation and an inoculation of seeds with bacterial preparation Yakut local strain CB No.1). The article provides the results of old-age cereal and bean and cereal herbage studies. Artificial herbage of the twelfth year of growth formed productivity of 1.4-2.5 t/hectare of dry matter at pasture use, with preservation of lucerne in herbage from 3 to 10%. At haying use productivity increase was obtained - 1.0 t/hectare of dry matter. High content of exchange energy (9.4 MJ) is noted at pasture use in variant with bean and cereal mix with lucerne subsowing (2004) + P60K60, at haying use in bean and cereal mix with subsowing of lucerne (2004) at a scarification + P60K60 it is 8.2 MJ. In old-age herbage the efficiency remains at the level of 1.1-1.6 feed units from hectare and 313-615 kg of crude protein.